The Role of Women in Community Development: Reenacting Digital Activism in Improving Education for All Children, Lesson Learned from Tulungagung and Semarang - Palupi Anggraheni; Anjani Tri Fatharini; Hanna Nurhaqiqi; Ratih Pandu Mustikasari; Yohana Grezia Diaz; Miracle Nauli Gultom (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2024)
Women have a significant role in ensuring the continuity of teaching andlearning activities in both the formal and non-formal sectors, particularlyregarding digital literacy challenges in early childhood education (3-6 yearsold). Especially considering the increased need for digital skills during andafter COVID-19. The potential for gadget addiction and abuse that leads toonline-based violence encourages the important role of the community inaligning challenges as well as opportunities for digitalization of earlychildhood education. Aligned with SDGs number 4 concerning qualityeducation. This research seeks for the red thread of the role of women as agentsin the development of community-based early learning methods, especially theimplementation of digital literacy. Primary data was taken from focusdiscussion group extraction, curriculum development, and joint monitoringevaluation on digital literacy, which was held at MI MuhammadiyahJunjung, Tulungagung Regency and Komunitas Harapan on the JoharMarket Riverside, Semarang. The concepts of Women in Development andDigital Literacy empowers women to contribute to development,cybersecurity, and children's rights. The results highlight structural issueslike poverty and gender inequality as barriers to educational quality acrossregions, further emphasizing the need for women educators in designingdigital literacy programs.